Reflections on time in “Alice in Wonderland”, by Lewis Carroll - Malheiros, Isaac (2023)
This article seeks to establish a dialogue between nonsense literature and Christian theology, focusing on Lewis Carroll's work "Alice in Wonderland." By closely examining the text and conducting a literature review, the article highlights themes with significant potential for theological discussion, notably the theme of time, an extensively debated subject during Carroll's era and one that he was well acquainted with. Exploring Carroll's narrative through the lens of Christian theology generates profound reflections on concepts like chronos and kairós, prompting discussions about the interplay between life's fleeting nature and the utilization of time. The article juxtaposes two concepts of time: the White Rabbit embodies relentless and urgent time, while the Mad Hatter embodies a subjective and pleasant time. Carroll's narrative encourages readers to engage in thought-provoking contemplations about time as they tumble into the surreal world of Wonderland.